The influence of aging on the methylation status of brain‐derived neurotrophic factor gene in blood. (28th June 2018) - Ihara, Kazushige; Fuchikami, Manabu; Hashizume, Masahiro; Okada, Satoshi; Kawai, Hisashi; Obuchi, Shuichi; Hirano, Hirohiko; Fujiwara, Yoshinori; Hachisu, Mitsugu; Hongyong, Kim; Morinobu, Shigeru
Abstract : Objective: Brain‐derived neurotrophic factor (BDNF) is involved in the pathophysiology of psychiatric disorders in adults and elderly individuals, and as a result, the DNA methylation (DNAm) of the BDNF gene in peripheral tissues including blood has been extensively examined to develop a useful biomarker for psychiatric disorders. However, studies to date have not previously investigated the effect of age on DNAm of the BDNF gene in blood. In this context, we measured DNAm of 39 CpG units in the CpG island at the promoter of exon I of the BDNF gene. Methods: We analyzed genomic DNA from peripheral blood of 105 health Japanese women 20 to 80 years of age to identify aging‐associated change in DNAm of the BDNF gene. In addition, we examined the relationship between total MMSE scores, numbers of stressful life events, and serum BDNF levels on DNAm of the BDNF gene. The DNAm rate at each CpG unit was measured using a MassArray ® system (Agena Bioscience), and serum BDNF levels were measured by ELISA. Results: There was a significant correlation between DNAm and age in 13 CpGs. However, there was no significant correlation between DNAm and total MMSE scores, numbers of life events, or serum BDNF levels. Conclusion: Despite the small number of subjects and the inclusion of only female subjects, our results suggest that DNAm of 13 CpGs of the BDNF gene may be an appropriate biomarker for aging and useful for predicting increased susceptibility to age‐related psychiatric disorders.